2010
DOI: 10.1007/s10546-010-9556-2
|View full text |Cite
|
Sign up to set email alerts
|

Large-Eddy Simulation for the Mechanism of Pollutant Removal from a Two-Dimensional Street Canyon

Abstract: Large-eddy simulation (LES) is conducted to investigate the mechanism of pollutant removal from a two-dimensional street canyon with a building-height to streetwidth (aspect) ratio of 1. A pollutant is released as a ground-level line source at the centre of the canyon floor. The mean velocities, turbulent fluctuations, and mean pollutant concentration estimated by LES are in good agreement with those obtained by wind-tunnel experiments. Pollutant removal from the canyon is mainly determined by turbulent motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 32 publications
(68 reference statements)
8
54
0
6
Order By: Relevance
“…Reynolds and Castro (2008) and Michioka et al (2011) investigated the occurrence of sweeps and ejections in the urban canopy by computing two-point correlations of u. However, the direct correlation between street-canyon ventilation and the flow was not made.…”
Section: The Mean Fluctuating Velocity Field For Street-canyon Ventilmentioning
confidence: 99%
See 1 more Smart Citation
“…Reynolds and Castro (2008) and Michioka et al (2011) investigated the occurrence of sweeps and ejections in the urban canopy by computing two-point correlations of u. However, the direct correlation between street-canyon ventilation and the flow was not made.…”
Section: The Mean Fluctuating Velocity Field For Street-canyon Ventilmentioning
confidence: 99%
“…Tomas et al (2016) show that up to 14h downstream of a rural-to-urban roughness transition the advective pollutant flux remains significant. Furthermore, Michioka et al (2011Michioka et al ( , 2014 conclude that street-canyon ventilation mostly takes place when low momentum regions pass over the canyon, and they suggest that these regions are of small scale compared to the coherent structures in the outer region and are generated close to the top of the canopy.…”
Section: Introductionmentioning
confidence: 99%
“…Please note that the definitions of ejections and sweeps here for turbulent pollutant flux are different from those for momentum flux due to the different transport processes of pollutant and momentum. Quadrant analysis of turbulent pollutant fluxes have shown that the ejections and sweeps dominate while sweeps contribute slightly more than ejections near the roof level [38], while Michioka et al [39] indicated that a large amount of pollutant is removed from the canyon by ejection due to the large-scale coherent structures. The turbulent intensity of the approaching flow could also directly influence pollutant removal from street canyons, as demonstrated in wind-tunnel experiments [34] and numerically [40].…”
Section: Flow and Dispersion Under Neutral Stratification Conditionsmentioning
confidence: 99%
“…Michioka et al [39] showed that the coherent structures close to the plane of the roof strongly affect pollutant removal from the street canyon. Therefore, changes in turbulent structures upwind of a street canyon where pollutants are emitted may cause different mech-anisms of pollutant removal (i.e., removal majorly by the mean or turbulent pollutant flux) when the street canyon geometry remains the same [41].…”
Section: Flow and Dispersion Under Neutral Stratification Conditionsmentioning
confidence: 99%
See 1 more Smart Citation